Constructing better health and wellbeing? Understanding structural constraints on promoting health and wellbeing in the UK construction industry - Hanna, ES; Markham, S (Emerald, 2019)
Purpose: The construction industry has high rates of work-related ill health. Whilst there have been more recent calls for a “health like safety” narrative within the industry, health has still predominantly been viewed via health risks rather than a more holistic conceptualisation of health and well-being. The workplace is viewed as a fruitful site for health promotion work, yet we know little about the possibilities and promise of health promotion within the construction industry. The paper aims to discuss these issues.